Implementing Product and Process Writing Approach on ESP Course for Freshmen at University - Prima Beauty Kartikasari (UPT P2M Politeknik Negeri Malang, 2023)
This article focuses on learning situations in an ESP classroom at a university. Having taught heterogeneous learners, the researcher found that many students still experience low learning achievement in writing lessons. Therefore, the researcher needs new ideas to prepare her students for a more meaningful writing experiences in classroom. I believe that adapting both product and process approach through collaborative writing tasks is one way to overcome the problem. To explain my arguments briefly, I would firstly describe the ESP course learner’s situation. Then, I will address the problem by reviewing some literature related to writing approaches in which I believe could help. Lastly, I will put the literature and implement it to my context. It is expected that having collaborative writing by using product-process approach can help my students experience a good learning experience with peers. Keywords: Product approach, process approach, collaborative writing, ESP course